Sulfide solid electrolyte and preparation method and application thereof

By introducing specific elements into the core of sulfide solid electrolyte and forming a hydrophobic layer, the stability and safety problems caused by the reaction of sulfide electrolyte with moisture are solved, and sulfide solid electrolyte with high air stability and good ion conductivity are achieved, thereby improving the circulation performance of all-solid lithium-ion batteries.

CN119627191APending Publication Date: 2025-03-14ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411824391.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Sulfide electrolytes are prone to react with moisture, resulting in material decomposition and reduced ionic conductivity, affecting the application performance of all-solid-state batteries, and the hydrogen sulfide gas generated by water reaction is toxic and corrosive, endangering the health of production personnel and equipment safety.

Method used

By introducing M elements, O elements and halogen elements into the sulfide solid electrolyte core, the intrinsic resistance to atmospheric degradation is increased, and a dense hydrophobic layer is introduced on its surface to block the contact between water molecules and the sulfide solid electrolyte core.

Benefits of technology

It significantly improves the air stability of sulfide solid electrolyte, reduces the production of toxic gases, maintains high ion conductivity, and improves the circulation performance of all-solid lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627191A_ABST
    Figure CN119627191A_ABST
Patent Text Reader

Abstract

The invention provides a sulfide solid-state electrolyte and a preparation method and application thereof. The sulfide solid-state electrolyte comprises a sulfide solid-state electrolyte inner core and a sulfide solid-state electrolyte outer core, and the hydrophobic layer is uniformly coated on the sulfide solid electrolyte core, and the hydrophobic layer comprises bis-hexadecyl phosphate. According to the sulfide solid-state electrolyte and the preparation method and application thereof, the air stability of the sulfide solid-state electrolyte can be remarkably improved, generation of toxic gas is reduced, the ionic conductivity of the sulfide solid-state electrolyte is not greatly reduced, the cycle performance of an all-solid-state lithium ion battery is improved, the manufacturing process is simple, and the cost is low. And the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a sulfide solid electrolyte and a preparation method and application thereof. Background Art

[0002] With the development of new energy technologies, all-solid-state batteries have received widespread attention as a new generation of efficient energy storage devices. Sulfide electrolyte materials have shown broad application prospects in all-solid-state batteries due to their high ionic conductivity and good mechanical properties. However, sulfide electrolytes react easily with water, resulting in material decomposition and a significant decrease in ionic conductivity, affecting their application performance in all-solid-state batteries. In addition, the hydrogen sulfide gas generated by the reaction with water is highly toxic and corrosive, endangering the health of production personnel and equipment safety. In addition, the production environment requirements are strict, which increases equipment investment and production costs. At present, the stability of sulfide electrolytes is improved by chemical modification, structural optimization, etc., but the improvement effect is limited, especially the stability under long-term exposure to humid environments is still not ideal. Summary of the invention

[0003] The present invention proposes a sulfide solid electrolyte and a preparation method and application thereof. The sulfide solid electrolyte and a preparation method and application thereof provided by the present invention can significantly improve the air stability of the sulfide solid electrolyte, reduce the generation of toxic gases, and do not significantly reduce the ion conductivity of the sulfide solid electrolyte, thereby improving the cycle performance of an all-solid-state lithium-ion battery, and the manufacturing process is simple and the cost is low.

[0004] To solve the above technical problems, the present invention is implemented through the following technical solutions.

[0005] The present invention provides a sulfide solid electrolyte, comprising at least:

[0006] a sulfide solid electrolyte core; and

[0007] A hydrophobic layer is uniformly coated on the sulfide solid electrolyte core, and the hydrophobic layer comprises dihexadecyl phosphate.

[0008] In one embodiment of the present invention, the thickness of the hydrophobic layer is 1 nm to 100 nm.

[0009] In one embodiment of the present invention, the chemical formula of the sulfide solid electrolyte core is Li a P 1-b M b S c O d X e, where 5 < a < 10, 0 < b < 1, 3 < c < 6, 0 < d < 2.5, 4 < c + d < 6, 0 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb, Mg, Sr, Ba, Zn, Cr, Sn, or Pb, and X is selected from one or more of Cl, Br, or I.

[0010] In one embodiment of the present invention, M is selected from Sb, In, Bi, or Mg, X is selected from Cl, and the value range of b is 0 < b ≤ 0.1.

[0011] The present invention also provides a method for preparing the sulfide solid electrolyte described above, which at least includes the following steps:

[0012] Add a hydrophobic agent to a solvent to form a modified solution;

[0013] Immerse the sulfide solid electrolyte core in the modified solution at a preset temperature for a first period of time; and

[0014] Take out the immersed sulfide solid electrolyte core and dry it under vacuum conditions.

[0015] In one embodiment of the present invention, the preset temperature is 0 - 60 °C, and the first period of time is 0.1 h - 10 h.

[0016] In one embodiment of the present invention, the solvent is selected from one or several of toluene, chlorobenzene, xylene, n - heptane, n - decane, n - hexane, ethylene glycol dimethyl ether, 1,2 - ethylenediamine, acetonitrile, tetrahydrofuran, acetone, ethyl acetate, benzyl acetate, butyl butyrate, or diisobutyl ketone. The hydrophobic agent includes dipalmitoyl phosphate, and the concentration of the hydrophobic agent in the modified solution is 0.01 mol / L - 0.5 mol / L.

[0017] In one embodiment of the present invention, the drying conditions include: the drying temperature is 25 °C - 300 °C, and the drying time is 0.1 h - 24 h.

[0018] The present invention also provides a all - solid - state lithium - ion battery, including:

[0019] A positive electrode plate;

[0020] A negative electrode plate;

[0021] A solid electrolyte membrane disposed between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane includes the sulfide solid electrolyte described above.

[0022] The present invention also provides an electronic device, including the all - solid - state lithium - ion battery described above.

[0023] In summary, the present invention proposes a sulfide solid electrolyte and its preparation method and application. By introducing M element, O element and halogen element into the core of the sulfide solid electrolyte, the intrinsic resistance to atmospheric degradation can be increased, and the production of toxic and harmful gases such as H2S can be effectively reduced. The core of the sulfide solid electrolyte has high stability and specific reactivity, which can improve the conductivity of the core of the sulfide solid electrolyte, enhance air stability and improve the electrolyte / active material interface properties, thereby improving compatibility with active materials. By introducing a dense hydrophobic layer on the surface of the core of the sulfide solid electrolyte, the contact between water molecules and the core of the sulfide solid electrolyte can be blocked, thereby significantly improving the air stability of the sulfide solid electrolyte. It is possible to form a sulfide solid electrolyte with an outer hydrophobic alkyl surface and an inner layer with high Li + The hydrophobic layer of the O=POLi covalent bond with a transmission coefficient has good chemical stability and ion conductivity, which can greatly improve the air stability of the sulfide solid electrolyte without significantly reducing the ion conductivity of the sulfide solid electrolyte, thereby improving the cycle performance of the all-solid-state lithium-ion battery. The formation process of the hydrophobic layer is simplified to form a uniformly coated hydrophobic layer, which has a simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0025] Figure 1 This is a 1C / 1C long cycle performance diagram of the all-solid-state lithium-ion battery in Example 3 at room temperature. DETAILED DESCRIPTION

[0026] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0027] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0028] The technical solutions of the present invention will be further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the scope of protection of the present invention.

[0029] The present invention provides a sulfide solid electrolyte, which at least includes a sulfide solid electrolyte core and a hydrophobic layer. The hydrophobic layer is uniformly coated on the sulfide solid electrolyte core. The hydrophobic layer includes, for example, dicetyl phosphate (DHP). By introducing a dense hydrophobic layer on the surface of the sulfide solid electrolyte core, the contact between water molecules and the sulfide solid electrolyte core can be blocked, thereby significantly improving the air stability of the sulfide solid electrolyte. Moreover, the hydrophobic layer has good chemical stability and ionic conductivity to ensure that the intrinsic properties of the sulfide solid electrolyte are not affected.

[0030] In an embodiment of the present invention, the chemical formula of the sulfide solid electrolyte core is, for example, Li a P 1-b M b S c O d X e , where 5 < a < 10, 0 < b < 1, 3 < c < 6, 0 < d < 2.5, 4 < c + d < 6, 0 < e < 2, M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb, Mg, Sr, Ba, Zn, Cr, Sn, or Pb, etc., and X is selected from one or more of Cl, Br, or I, etc. Introducing M element, O element, and halogen element into the sulfide solid electrolyte core can increase the inherent resistance to atmospheric degradation, effectively reduce the generation of toxic and harmful gases such as H2S, promote the rapid movement of lithium ions and the uniform distribution of the electric field, prevent the formation of lithium dendrites at the same time, enhance the air stability and chemical stability of the sulfide solid electrolyte core, and improve the life and safety of all-solid-state lithium-ion batteries and lithium batteries.

[0031] In one embodiment of the present invention, M is selected from one or more of Sb, In, Bi or Mg elements, and the bonds such as Sb-S / Bi-S / In-S / Mg-S formed are difficult to be damaged by external influences, so that the core of the sulfide solid electrolyte has high stability and specific reactivity, and can improve the conductivity of the core of the sulfide solid electrolyte, enhance air stability and improve the electrolyte / active material interface properties, thereby improving compatibility with the active material. X is selected from Cl, for example, to improve the ionic conductivity and electrochemical stability of the core of the sulfide solid electrolyte and improve voltage stability. The value range of b is 0<b≤0.1. When the doping amount is too low, the improvement effect is not obvious. Excessive doping will cause excessive lattice distortion and destroy the original crystal structure, which may lead to a decrease in the structural stability of the material, and even phase separation or amorphization, thereby reducing the ionic conductivity of the material. In one embodiment of the present invention, when M is +5, b is optimally 0.04, when M is +3, b is optimally 0.02, and when M is +2, b is optimally 0.02, so that the battery capacity, number of cycles and energy density of the lithium-ion battery are optimized.

[0032] In one embodiment of the present invention, the thickness of the hydrophobic layer is, for example, 1 nm to 100 nm, and the thickness of the hydrophobic layer is tested, for example, by a scanning electron microscope or a transmission electron microscope. When the hydrophobic layer is too thin, it is not enough to improve the air stability of the sulfide solid electrolyte core. When the hydrophobic layer is too thick, the outer hydrophobic alkyl surface will greatly prevent the transmission of lithium ions, and the conductivity of the electrolyte will be seriously reduced, thereby affecting the battery performance. By forming a hydrophobic layer on the sulfide solid electrolyte core, the DHP molecules are first adsorbed on the surface of the sulfide solid electrolyte core, and then the sulfide solid electrolyte core and the inner layer of the DHP molecules produce a condensation reaction to form an O=POLi covalent bond, forming an outer hydrophobic alkyl surface and an inner layer with a high Li + The hydrophobic layer of the O=POLi covalent bond with a transmission coefficient. The hydrophobic layer can greatly improve the air stability of the sulfide solid electrolyte without significantly reducing the ionic conductivity of the sulfide solid electrolyte. In one embodiment of the present invention, after the sulfide solid electrolyte with a hydrophobic layer is exposed to a dry room at -40°C for 24 hours, the ionic conductivity retention rate is, for example, 55% to 95%. Further, the type of the sulfide solid electrolyte core and the thickness of the hydrophobic layer are controlled. The ionic conductivity retention rate of the sulfide solid electrolyte after being exposed to a dry room at -40°C for 24 hours is, for example, 81% to 95%, which can greatly improve the air stability of the sulfide solid electrolyte.

[0033] The present invention also proposes a method for preparing a sulfide solid electrolyte, which comprises at least the following steps: adding a hydrophobic agent into a solvent to prepare a modified solution; soaking a sulfide solid electrolyte core in the modified solution at a preset temperature for a first time; taking out the soaked sulfide solid electrolyte core and drying it under vacuum conditions.

[0034] In one embodiment of the present invention, the solvent is selected from one or more of toluene, chlorobenzene, xylene, n-heptane, n-decane, n-hexane, glycol dimethyl ether, 1,2-ethylenediamine, acetonitrile, tetrahydrofuran, acetone, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone, and the hydrophobic agent includes, for example, dihexadecyl phosphate, and the concentration of the hydrophobic agent in the modified solution is, for example, 0.01 mol / L to 0.5 mol / L.

[0035] In one embodiment of the present invention, the sulfide solid electrolyte core is obtained according to the following method: According to the chemical formula of the sulfide solid electrolyte core Li a P 1-b M b S c O d X e , after the Li source, P source, M source, S source and X source are mixed evenly according to the stoichiometric amount, they are added to a ball mill, and after ball milling, they are calcined to obtain a sulfide solid electrolyte core material. Wherein, the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S, etc., the P source is selected from one or more of simple P, P2S5, P4S6, PCl5 or PBr5, etc., the M source is selected from one or more of M oxides or M sulfides, the S source is selected from one or more of simple S, Li2S, P2S5 or M sulfides, etc., the X source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, etc., and the O element in the chemical formula comes from the oxide of M. After the raw materials are mixed evenly, they are placed in a ball mill and ball milled in an inert gas atmosphere, wherein the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50rpm to 1000rpm, and the ball milling time is, for example, 1h to 48h. After ball milling, the mixed raw materials are calcined at 400° C. to 600° C. for 1 h to 18 h to obtain a sulfide solid electrolyte core.

[0036] In one embodiment of the present invention, the sulfide solid electrolyte core is immersed in a modified solution at a preset temperature for a first time, wherein the preset temperature is, for example, 0 to 60°C, and the first time is, for example, 0.1h to 10h, to control the thickness of the formed hydrophobic layer. The soaked sulfide solid electrolyte core is taken out and dried under vacuum conditions, wherein the drying temperature is, for example, 25°C to 300°C, and the drying time is, for example, 0.1h to 24h. A uniformly coated hydrophobic layer can be formed on the surface of the sulfide solid electrolyte core material by a simple immersion method, and the preparation process is simple and the cost is low.

[0037] The present invention also proposes an all-solid-state lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the solid electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane comprises the above-mentioned sulfide solid electrolyte to improve the cycle performance of the all-solid-state lithium-ion battery. In one embodiment of the present invention, the solid electrolyte membrane is obtained by, for example, cold pressing the above-mentioned sulfide solid electrolyte at a pressure of 300MPa to 400MPa, and the thickness of the solid electrolyte membrane is, for example, 100μm to 500μm. In the present invention, the all-solid-state lithium-ion battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the types and types of the all-solid-state lithium-ion battery.

[0038] In one embodiment of the present invention, the positive electrode sheet includes, for example, a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric, and the thickness of the positive electrode current collector is, for example, 8 μm to 15 μm.

[0039] In one embodiment of the present invention, the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a positive electrode conductor, and a positive electrode binder, wherein the positive electrode active material is, for example, selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO), or lithium nickel cobalt aluminum oxide (NCA), the positive electrode electrolyte is, for example, a halide solid electrolyte, the positive electrode conductor is, for example, selected from at least one of graphite, graphene, conductive carbon black (Super P), nanocarbon fiber (Vapor-grown Carbon Fiber, VGCF), or carbon nanotubes, and the positive electrode binder is, for example, selected from polyvinylidene fluoride (Polyvinylidene Fluoride, PVDF), carboxymethyl cellulose (Carboxymethyl Cellulose, CMC), styrene butadiene rubber (Polymerized Styrene Butadiene Rubber, SBR), polyvinyl pyrrolidone (Polyvinyl pyrrolidone, PVP), polymethyl methacrylate (Polymethyl methacrylate, PVP), and polyvinyl pyrrolidone (PVP). Methacrylate, PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane (PU), polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer (EPDM), styrene-butadiene rubber, fluorine rubber (Fluororubber), β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (Ethylene-chlorotrifluoroethylene copolymer, ECTFE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) or polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE).

[0040] In one embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, and the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, the positive electrode electrolyte is for example Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , the positive electrode conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P and VGCF is, for example, 1:1, and the positive electrode binder is, for example, PTFE. After the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent and the positive electrode binder are uniformly mixed in a mass ratio of, for example, 69:29:1:1, they are compounded with aluminum foil by dry pressing to obtain a positive electrode sheet. The present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent and the positive electrode binder, which can be selected according to actual needs, and the positive electrode current collector can be not provided as needed.

[0041] In one embodiment of the present invention, the negative electrode plate is selected from at least one of a metal lithium plate, a metal indium plate or a lithium indium alloy plate. In another embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode current collector and a negative electrode active layer coated on the surface of at least one side of the negative electrode current collector. The negative electrode current collector is, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector or a stainless steel current collector, and the thickness of the negative electrode current collector is, for example, 8 μm to 15 μm.

[0042] In one embodiment of the present invention, the negative electrode active layer includes, for example, a negative electrode active material, a negative electrode electrolyte, a negative electrode conductive agent and a negative electrode binder, wherein the negative electrode active material is selected from at least one of a graphite material or a silicon-containing material, and the silicon-containing material is, for example, at least one of a silicon material, a silicon-oxygen material or a silicon-carbon material, and the negative electrode electrolyte is, for example, a sulfide electrolyte, and the negative electrode conductive agent is selected from at least one of graphite, graphene, Super P, VGCF or carbon nanotubes, and the negative electrode binder is selected from at least one of PVDF, CMC, SBR, PVP, PMMA, PAN, PAA, PU, ​​PVA, Alg, EPDM, styrene-butadiene rubber, fluororubber, β-CDp, LA132, PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, PVDF-HFP or PVDF-CTFE.

[0043] In one embodiment of the present invention, the negative electrode current collector is, for example, copper foil, the negative electrode active material is, for example, a mixture of silicon oxide material and graphite, and the ratio of silicon oxide material to graphite is, for example, 5:95, the negative electrode electrolyte is, for example, the above-mentioned sulfide solid electrolyte, the negative electrode conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1, and the negative electrode binder is, for example, SBR. After the negative electrode active material, the negative electrode electrolyte, the negative electrode conductive agent, the negative electrode binder and the thickener are mixed evenly in a mass ratio of, for example, 72:22:3:3, they are compounded with the copper foil by dry pressing to obtain the negative electrode sheet. The present invention does not limit the mass ratio of the negative electrode active material, the negative electrode electrolyte, the negative electrode conductive agent and the negative electrode binder, which can be selected according to actual needs, and the negative electrode current collector can be provided as needed.

[0044] In one embodiment of the present invention, the above-mentioned positive electrode sheet, solid electrolyte membrane sheet and negative electrode sheet are placed in sequence, pressed and sealed to obtain an all-solid-state lithium-ion battery. The assembly process of the all-solid-state battery is completed in an inert atmosphere glove box.

[0045] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0046] Example 1

[0047] Preparation of solid electrolyte membrane: Under argon atmosphere, 2 mol of Li2S, 1.5 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 were added into a ball mill with a ball-to-material ratio of 30:1 and a rotation speed of 500 rpm for 20 h. Then, the mixed raw materials obtained by ball milling were sintered at 500 °C for 10 h to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Sulfide solid electrolyte core. DHP was added to butyl butyrate solution to prepare a 0.01 mol / L DHP solution. The sulfide solid electrolyte core was added to the DHP solution and soaked for 1 hour at 25°C. After soaking, it was filtered and then placed in a vacuum oven at 80°C for 12 hours to remove the residual solvent to obtain a moisture-resistant sulfide solid electrolyte with a DHP hydrophobic layer. Cold pressing was performed at a pressure of 350 MPa to obtain a 300 μm thick solid electrolyte membrane.

[0048] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1O2, positive electrode conductive agent, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , PTFE are mixed evenly in a mass ratio of 69:29:1:1, and then compounded with aluminum foil by dry pressing, and cut into discs with a diameter of 10 mm to obtain a positive electrode sheet. The positive electrode conductive agent includes Super P and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1.

[0049] Selection of negative electrode sheets: Select single-element lithium sheets and cut them into discs with a diameter of 10 mm to obtain negative electrode sheets.

[0050] All-solid-state lithium-ion battery assembly: The positive electrode sheet, solid electrolyte membrane sheet and negative electrode sheet prepared above are stacked in sequence, pressed and sealed, and assembled into an all-solid-state lithium-ion battery.

[0051] Example 2

[0052] The concentration of the DHP solution was 0.05 mol / L, and other operations were consistent with those in Example 1.

[0053] Example 3

[0054] The concentration of the DHP solution was 0.1 mol / L, and other operations were consistent with those in Example 1.

[0055] Example 4

[0056] The concentration of the DHP solution was 0.2 mol / L, and other operations were consistent with those in Example 1.

[0057] Example 5

[0058] The concentration of the DHP solution was 0.5 mol / L, and other operations were consistent with those in Example 1.

[0059] Example 6

[0060] The electrolyte was immersed in the DHP solution for 0.1 h, and other operations were consistent with those in Example 1.

[0061] Example 7

[0062] The electrolyte was immersed in the DHP solution for 0.5 h, and other operations were consistent with those in Example 1.

[0063] Example 8

[0064] The electrolyte was immersed in the DHP solution for 5 h, and other operations were consistent with those in Example 1.

[0065] Example 9

[0066] The electrolyte was immersed in the DHP solution for 10 h, and other operations were consistent with those in Example 1.

[0067] Example 10

[0068] The chemical formula of the sulfide solid electrolyte core prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of Sb2O5 is Li 5.5 P 0.99 Sb 0.01 S 4.475 O 0.025 Cl 1.5 , other operations remain the same as those in Example 3.

[0069] Embodiment 11

[0070] The chemical formula of the sulfide solid electrolyte core prepared by 2 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.03 mol Sb2O5 is Li 5.5 P 0.94 Sb 0.06 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.

[0071] Example 12

[0072] The chemical formula of the sulfide solid electrolyte core prepared by 2 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.05 mol Sb2O5 is Li 5.5 P 0.9 Sb 0.1 S 4.25 O 0.25 Cl 1.5 , other operations remain the same as those in Example 3.

[0073] Embodiment 13

[0074] The chemical formula of the sulfide solid electrolyte core prepared by 2 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.48 mol P2S5, and 0.02 mol Sb2O5 is Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.3 Br 0. 1I0.1 , other operations remain the same as those in Example 3.

[0075] Embodiment 14

[0076] The chemical formula of the sulfide solid electrolyte core prepared by 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.005 mol In2O3 is Li 5.52 P 0.99 In 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 3.

[0077] Embodiment 15

[0078] The chemical formula of the sulfide solid electrolyte core prepared by 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 3.

[0079] Example 16

[0080] The chemical formula of the sulfide solid electrolyte core prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.03 mol In2O3 is Li 5.62 P 0.94 In 0.06 S 4.41 O 0.09 Cl 1.5 , other operations remain the same as those in Example 3.

[0081] Embodiment 17

[0082] The chemical formula of the sulfide solid electrolyte core prepared by 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.05 mol In2O3 is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.

[0083] Embodiment 18

[0084] The chemical formula of the sulfide solid electrolyte core prepared by 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 , other operations remain the same as those in Example 3.

[0085] Embodiment 19

[0086] The chemical formula of the sulfide solid electrolyte core prepared by 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.005 mol Bi2O3 is Li 5.52 P 0.99 Bi 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 3.

[0087] Embodiment 20

[0088] The chemical formula of the sulfide solid electrolyte core prepared by 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 3.

[0089] Embodiment 21

[0090] The chemical formula of the sulfide solid electrolyte core prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.03 mol Bi2O3 is Li 5.62 P 0.94 Bi 0.06 S 4.41 O 0.09 Cl 1.5 , other operations remain the same as those in Example 3.

[0091] Embodiment 22

[0092] The chemical formula of the sulfide solid electrolyte core prepared by 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.05 mol Bi2O3 is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.

[0093] Embodiment 23

[0094] The chemical formula of the sulfide solid electrolyte core prepared by 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 , other operations remain the same as those in Example 3.

[0095] Embodiment 24

[0096] The chemical formula of the sulfide solid electrolyte core prepared by 2.015 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.01 mol MgO is Li 5.53 P 0.99 Mg 0.01 S 4.49 O 0.01 Cl 1.5 , other operations remain the same as those in Example 3.

[0097] Embodiment 25

[0098] The chemical formula of the sulfide solid electrolyte core prepared by 2.03 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5 , other operations remain the same as those in Example 3.

[0099] Embodiment 26

[0100] The chemical formula of the sulfide solid electrolyte core prepared by 2.09 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.06 mol MgO is Li 5.68 P 0.94 Mg 0.06 S 4.44 O 0.06 Cl 1.5 , other operations remain the same as those in Example 3.

[0101] Embodiment 27

[0102] The chemical formula of the sulfide solid electrolyte core prepared by 2.15 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.1 mol MgO is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 , other operations remain the same as those in Example 3.

[0103] Embodiment 28

[0104] The chemical formula of the sulfide solid electrolyte core prepared by 2.03 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.02 mol MgO is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.3 Br 0.1 I 0.1 , other operations remain the same as those in Example 3.

[0105] Comparative Example 1

[0106] The chemical formula of the sulfide solid electrolyte core prepared by 2 mol of Li2S, 1.5 mol of LiCl, and 0.5 mol of P2S5 is Li 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 3.

[0107] Comparative Example 2

[0108] The core of the sulfide solid electrolyte Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5Add to butyl butyrate solution and soak for 1 hour. After soaking, filter and then place in a vacuum oven at 80°C for 12 hours to remove residual solvent to obtain a sulfide solid electrolyte. Cold press at a pressure of 350MPa to obtain a 300μm thick solid electrolyte membrane. Other operations are consistent with Example 1.

[0109] Comparative Example 3

[0110] The concentration of the DHP solution was 1 mol / L, and other operations were consistent with those in Example 1.

[0111] In the present invention, different sulfide solid electrolyte cores and preparation methods are used to obtain sulfide solid electrolytes and all-solid-state lithium-ion batteries in Examples 1-28 and Comparative Examples 1-3. Some preparation conditions and properties of sulfide solid electrolytes are shown in Table 1. Under a 25°C environment, the above-prepared all-solid-state lithium-ion battery is subjected to long-cycle charge and discharge, its discharge capacity is measured, and the energy density is calculated. Among them, the operating voltage range of the battery test is 2.5V-4.3V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded, which is the 1C discharge capacity. When the battery capacity reaches 80% (80% State of Health, 80% SOH) of the first cycle capacity, the test is terminated to obtain the number of cycles at room temperature. The test results are shown in Table 2.

[0112] Table 1. Partial preparation conditions and properties of sulfide solid electrolytes in Examples 1-28 and Comparative Examples 1-3

[0113]

[0114] Table 2 Performance test results of all-solid-state lithium-ion batteries in Examples 1-28 and Comparative Examples 1-3

[0115]

[0116] Please refer to Table 1 and Table 2. By comparing Examples 1-5 and Comparative Examples 2-3, it can be seen that as the concentration of the DHP solution increases, the thickness of the hydrophobic layer increases with the same soaking time. The ionic conductivity retention rate of the sulfide solid electrolyte after being exposed to a -40°C dry room for 24 hours gradually increases, and the cycle performance of the all-solid-state lithium-ion battery gradually increases and then gradually decreases. This is because the thicker the hydrophobic layer, the better the air stability of the sulfide solid electrolyte, the better the chemical stability and ionic conductivity of the sulfide solid electrolyte, the appearance of the hydrophobic layer can reduce the interface side reactions between the electrolyte and the positive / negative active materials, and the inner layer O=POLi covalent bond can improve the Li + However, when the hydrophobic layer is too thick, the hydrophobic alkyl surface of the outer layer will greatly hinder the transmission of lithium ions, and the conductivity of the electrolyte will be seriously reduced, thus affecting the battery performance.

[0117] Please refer to Table 1 and Table 2. By comparing Example 3 and Examples 6-9, it can be seen that when the concentration of the DHP solution is the same, as the immersion time of the sulfide solid electrolyte core in the DHP solution increases, the thickness of the hydrophobic layer becomes larger and larger, and the ionic conductivity retention rate of the sulfide solid electrolyte after being exposed to a -40°C dry room for 24 hours gradually increases. When the thickness of the hydrophobic layer is greater than 60nm, the ionic conductivity retention rate tends to be stable. At the same time, the cycle performance of the all-solid-state lithium-ion battery gradually increases and then gradually decreases.

[0118] See also Figure 1 As shown, at a current density of 1C, the all-solid-state lithium-ion battery in Example 3 still has an energy storage capacity of about 140 mAh / g after 985 cycles, indicating that the sulfide solid electrolyte has excellent reaction kinetics and cycle stability, and has good hydrophobicity. The obtained solid electrolyte membrane has a good gain effect on the cycle stability and reaction activity specific capacity of the battery. The all-solid-state lithium-ion battery has excellent specific capacity, rate performance and cycle life.

[0119] Please refer to Table 1 and Table 2. Comparative Examples 3 and 10-12 show that as the doping amount of the Sb element in the sulfide solid electrolyte core increases, the ionic conductivity retention rate of the sulfide solid electrolyte after being exposed to a -40°C dry room for 24 hours increases and then tends to be stable, and the cycle performance of the all-solid-state lithium-ion battery gradually increases and then gradually decreases. Comparative Examples 14-17 show that as the doping amount of the In element in the sulfide solid electrolyte core increases, the ionic conductivity retention rate of the sulfide solid electrolyte after being exposed to a -40°C dry room for 24 hours increases and then tends to be stable, and the cycle performance of the all-solid-state lithium-ion battery gradually increases and then gradually decreases. Comparative Examples 19-22 show that as the doping amount of the Bi element in the sulfide solid electrolyte core increases, the ionic conductivity retention rate of the sulfide solid electrolyte after being exposed to a -40°C dry room for 24 hours increases and then tends to be stable, and the cycle performance of the all-solid-state lithium-ion battery first gradually increases and then gradually decreases. Comparative Examples 24-27 show that, with the increase in the amount of Mg element doping in the sulfide solid electrolyte core, the ionic conductivity retention rate of the sulfide solid electrolyte after being exposed to -40 ° C dry room for 24h increases and tends to be stable, and the cycle performance of the all-solid-state lithium ion battery first increases gradually and then gradually decreases. This is because, when the M doping amount in the sulfide solid electrolyte core is too low, the improvement effect of the stability of the sulfide solid electrolyte core itself is not obvious, and the cycle performance is poor. When the doping amount of M in the sulfide solid electrolyte core is within a suitable range, the hydrophobic layer is matched to improve the chemical stability and ionic conductivity of the sulfide solid electrolyte, and improve the cycle performance of the all-solid-state lithium ion battery. When the doping amount of M in the sulfide solid electrolyte core is too large, excessive doping will cause the lattice distortion to be too large, destroying the original crystal structure, which may cause the structural stability of the material to decrease, thereby the chemical stability and ionic conductivity of the sulfide solid electrolyte decrease, and the cycle performance of the all-solid-state lithium ion battery decreases.

[0120] Please refer to Table 1 and Table 2. By comparing Examples 3 and 13, Examples 15 and 18, Examples 20 and 23, and Examples 25 and 28, it can be seen that when the doping amounts of Sb, In, Bi or Mg in the core of the sulfide solid electrolyte are the same, the ionic conductivity retention rate of the sulfide solid electrolyte after being exposed to a -40°C dry room for 24 hours is reduced by doping with Br and I elements, and the cycle performance of the battery is also reduced.

[0121] Please refer to Table 1 and Table 2. By comparing Example 3, Example 15, Example 20, Example 2 and Comparative Example 1, it can be seen that when the sulfide solid electrolyte is not doped with M element and O element, the battery has almost no cycle performance and short circuit occurs quickly.

[0122] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state lithium-ion batteries, and the all-solid-state lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state lithium-ion battery, and therefore includes the advantages of the above-mentioned all-solid-state lithium-ion battery, which will not be elaborated here.

[0123] In summary, the present invention proposes a sulfide solid electrolyte and its preparation method and application. By introducing M element, O element and halogen element into the core of the sulfide solid electrolyte, the intrinsic resistance to atmospheric degradation can be increased, and the production of toxic and harmful gases such as H2S can be effectively reduced. The core of the sulfide solid electrolyte has high stability and specific reactivity, which can improve the conductivity of the core of the sulfide solid electrolyte, enhance air stability and improve the electrolyte / active material interface properties, thereby improving compatibility with active materials. By introducing a dense hydrophobic layer on the surface of the core of the sulfide solid electrolyte, the contact between water molecules and the core of the sulfide solid electrolyte can be blocked, thereby significantly improving the air stability of the sulfide solid electrolyte. It is possible to form a sulfide solid electrolyte with an outer hydrophobic alkyl surface and an inner layer with high Li + The hydrophobic layer of the O=POLi covalent bond with a high transmission coefficient has good chemical stability and ion conductivity, which can greatly improve the air stability of the sulfide solid electrolyte without significantly reducing the ion conductivity of the sulfide solid electrolyte, thereby improving the cycle performance of the all-solid-state lithium-ion battery. The uniform hydrophobic layer coating on the surface of the sulfide solid electrolyte can be achieved through a simple immersion method, which is simple in process and low in cost.

[0124] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0125] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A sulfide solid electrolyte, characterized in that: At least: Sulfide solid electrolyte core; as well as A hydrophobic layer is uniformly coated on the sulfide solid electrolyte core, and the hydrophobic layer comprises dihexadecyl phosphate.

2. The sulfide solid electrolyte according to claim 1, characterized in that The thickness of the hydrophobic layer is 1 nm to 100 nm.

3. The sulfide solid electrolyte according to claim 1, characterized in that The chemical formula of the sulfide solid electrolyte core is Li a P 1-b M b S c O d X e , where 5 < a < 10, 0 < b < 1, 3 < c < 6, 0 < d < 2.5, 4 < c + d < 6, 0 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb, Mg, Sr, Ba, Zn, Cr, Sn or Pb, and X is selected from one or more of Cl, Br or I.

4. The sulfide solid electrolyte according to claim 3, characterized in that M is selected from Sb, In, Bi or Mg, X is selected from Cl, and the value range of b is 0 <b≤0.1。 5. A method for preparing the sulfide solid electrolyte according to any one of claims 1 to 4, characterized in that: At least the following steps are included: adding a hydrophobic agent into a solvent to prepare a modified solution; immersing the sulfide solid electrolyte core in the modified solution at a preset temperature for a first time; as well as The sulfide solid electrolyte core is taken out after soaking and dried under vacuum conditions.

6. The method for preparing a sulfide solid electrolyte according to claim 5, characterized in that: The preset temperature is 0-60° C., and the first time is 0.1 h-10 h.

7. The method for preparing a sulfide solid electrolyte according to claim 5, characterized in that: The solvent is selected from one or more of toluene, chlorobenzene, xylene, n-heptane, n-decane, n-hexane, glycol dimethyl ether, 1,2-ethylenediamine, acetonitrile, tetrahydrofuran, acetone, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone, the hydrophobic agent includes dihexadecyl phosphate, and the concentration of the hydrophobic agent in the modified solution is 0.01 mol / L to 0.5 mol / L.

8. The method for preparing a sulfide solid electrolyte according to claim 5, characterized in that: The drying conditions include: a drying temperature of 25° C. to 300° C. and a drying time of 0.1 h to 24 h.

9. An all-solid-state lithium-ion battery, characterized in that: include: Positive electrode; Negative electrode; A solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane comprises the sulfide solid electrolyte according to any one of claims 1 to 4.

10. An electronic device, characterized in that: Including the all-solid-state lithium-ion battery as described in claim 9.

Citation Information

Patent Citations

  • All-solid-state lithium ion battery and preparation method thereof

    CN108063278A

  • Sulfide solid electrolyte material, preparation method thereof and solid-state battery

    CN111129579A

  • Preparation method of all-solid-state sulfide electrolyte for lithium ion battery

    CN112421119A

  • All-solid secondary battery binder composition, all-solid secondary battery slurry composition, solid-electrolyte-containing layer, and all-solid secondary battery

    CN112703626A

  • Sulfide solid electrolyte material and preparation method thereof

    CN115275332A